Predictors and consequences of health anxiety symptoms: a novel twin modeling study. (15th January 2018) - López‐Solà, C.; Bui, M.; Hopper, J. L; Fontenelle, L. F.; Davey, C. G.; Pantelis, C.; Alonso, P.; van den Heuvel, O. A.; Harrison, B. J.
Abstract : Objective: The question of how to best conceptualize health anxiety (HA) from a diagnostic and etiological perspective remains debated. The aim was to examine the relationship between HA and the symptoms of anxiety and obsessive–compulsive‐related disorders in a normative twin population. Method: Four hundred and ninety‐six monozygotic adult twin pairs from the Australian Twin Registry participated in the study (age, 34.4 ± 7.72 years; 59% females). Validated scales were used to assess each domain. We applied a twin regression methodology—ICE FALCON—to determine whether there was evidence consistent with 'causal' relationships between HA and other symptoms by fitting and comparing model estimates. Results: Estimates were consistent with higher levels of obsessing ('unwanted thoughts') ( P = 0.008), social anxiety ( P = 0.03), and body dysmorphic symptoms ( P = 0.008) causing higher levels of HA symptoms, and with higher levels of HA symptoms causing higher levels of physical/somatic anxiety symptoms ( P = 0.001). Conclusion: Obsessional thoughts, body dysmorphic concerns, and social anxiety symptoms may have a causal influence on HA. To report physical/somatic anxiety appears to be a consequence of the underlying presence of HA‐related fears. Should our results be confirmed by longitudinal studies, the evaluation and treatment of HA may benefit from the consideration of these identified risk factors.